2020
DOI: 10.1021/acscatal.0c03218
|View full text |Cite
|
Sign up to set email alerts
|

Tris(pentafluorophenyl)borane-Catalyzed Cyclopropanation of Styrenes with Aryldiazoacetates

Abstract: Methods for the synthesis of cyclopropanes are critical for drug discovery, chemical biology, total synthesis, and other fields. Herein, we report the use of the strong sterically encumbered Lewis acid tris­(pentafluorophenyl)­borane as a catalyst for the cyclopropanation of unactivated alkenes using aryldiazoacetates. The cyclopropane products are synthesized using 10 mol % of the catalyst under mild conditions in up to 90% yield (8:1 to >20:1 dr). We propose that the reaction proceeds via a Lewis acid-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 72 publications
4
41
0
1
Order By: Relevance
“…Owing to its strong acidity, B(C 6 F 5 ) 3 is often used as an organic catalyst in many types of chemical reactions. [17][18][19] Thus a large number of theoretical and experimental studies of triel bonds have appeared in recent years. [20][21][22][23][24] These studies have revealed a number of unusual characteristics of triel bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its strong acidity, B(C 6 F 5 ) 3 is often used as an organic catalyst in many types of chemical reactions. [17][18][19] Thus a large number of theoretical and experimental studies of triel bonds have appeared in recent years. [20][21][22][23][24] These studies have revealed a number of unusual characteristics of triel bonds.…”
Section: Introductionmentioning
confidence: 99%
“…More applications of triel bonds are found in assorted chemical reactions. Owing to its strong acidity, B(C 6 F 5 ) 3 is often used as an organic catalyst in many types of chemical reactions [17–19] . Thus a large number of theoretical and experimental studies of triel bonds have appeared in recent years [20–24] …”
Section: Introductionmentioning
confidence: 99%
“…Kürzlich haben wir [5] und andere [6a] die katalytische Aktivität von B(C 6 F 5 ) 3 bei der Aktivierung von Diazoestern untersucht, die zur Bildung von Carben‐Zwischenprodukten durch die Abspaltung von N 2 führt. Die Carben‐Zwischenprodukte können anschließend als Bausteine für die Synthese neuartiger organischer Moleküle durch eine Reihe verschiedener Reaktionen wie O‐H/N‐H/C‐H‐Insertion, [5a, 6b,d,g,h] Azid/Carbonat‐Transfer, [6e,f] Cyclopropanierung/Cyclopropenierung [5a, 6c] und für die Ringöffnung heterocyclischer Verbindungen verwendet werden [5a] . In dieser Studie interessierten wir uns für die B(C 6 F 5 ) 3 ‐katalysierte Synthese von Pyrazolen aus Vinyldiazoacetaten, bei der die N 2 ‐Funktionalität des Diazo‐Ausgangsmaterials nicht freigesetzt wird.…”
Section: Methodsunclassified
“…Carbene transfer reactions are one of the most fundamental reactions in organic synthesis and widespread studies have been conducted to explore the synthetic utility of carbenes for making a variety of novel compounds. 11 Recently, we 12 and Wilkerson-Hill 13 observed that catalytic amounts of B(C6F5)3 enable the cyclopropanation reactions of styrenes (Scheme 1A) using α-aryl α-diazoesters. This exciting outcome motivated us to investigate this reactivity further to see if arylacetylenes could also be used as substrates in reactions with α-aryl αdiazoesters using B(C6F5)3 as a catalyst.…”
mentioning
confidence: 99%